Septal protein SepJ from the heterocyst‐forming cyanobacterium Anabaena forms multimers and interacts with peptidoglycan - Ramos‐León, Félix (FEBS Open Bio, 2017)
Heterocyst‐forming cyanobacteria grow as filaments that can be hundreds of cells long. Proteinaceous septal junctions provide cell–cell binding and communication functions in the filament. In Anabaena sp. strain PCC 7120, the SepJ protein is important for the formation of septal junctions. SepJ consists of integral membrane and extramembrane sections – the latter including linker and coiled‐coil domains. SepJ (predicted MW, 81.3 kDa) solubilized from Anabaena membranes was found in complexes of about 296–334 kDa, suggesting that SepJ forms multimeric complexes. We constructed an Anabaena strain producing a double‐tagged SepJ protein (SepJ‐GFP‐His(10)) and isolated the tagged protein by a two‐step affinity chromatography procedure. Analysis of the purified protein preparation provided no indication of the presence of specific SepJ partners, but suggested that SepJ is processed to remove an N‐terminal fragment. Additionally, pull‐down experiments showed that His(6)‐tagged versions of SepJ and of the SepJ coiled‐coil domain interact with Anabaena peptidoglycan (PG). Our results indicate that SepJ forms multimers, that it interacts with PG, and that the coiled‐coil domain is involved in this interaction. These observations support the idea that SepJ is a component of the septal junctions that join the cells in the Anabaena filament.